Astragalus sp. - Yakuboğulları, Nilgün; Bedir, Erdal; Bedir, Erdal; Yakuboğulları, Nilgün (CRC Press, 2023)
Astragalus is one of the largest genera in Turkey and is widely distributed worldwide. The phytochemical studies on Turkish Astragalus species have presented 112 new compounds besides 63 known compounds. The overriding basis for biological activity studies is the traditional use of Astragalus roots in the Southeastern Region of Turkey to cure leukemia. As the isolated compounds did not show cytotoxic properties, a hypothesis that the biological activity of Astragalus saponins might result from the activation of the immune system came up. While Astragalus polysaccharides are used for their strong immunomodulatory activities in Chinese medicine, there are a few articles revealing the immunostimulatory properties of Astragalus saponins. Here, we summarized the compounds isolated from Turkish Astragalus species and concentrated on the immunomodulatory activities of these compounds to put forward their potential as saponin-based vaccine adjuvants. © 2024 selection and editorial matter, Ufuk Koca-Caliskan; individual chapters, the contributors.